A Defense of Moderate Language Pluralism in Scholarly Production in the Humanities - Perez, Diana Ines (2020)
In this paper we argue in favor of a moderate language plurilingualism in scholarly production in the humanities. We start by proposing some desiderata that a good policy regarding language use in the humanities should meet. We then survey institutional/policy options regarding the use of languages in the humanities and argue that different versions of monolingualism fall short of satisfying the desiderata. As a result, we consider different alternatives supporting plurilingualism and we defend that one of the options, that we call Moderate Language Pluralism or Moderate Plurilingualism, does better than the others vis-à-vis the desiderata. Finally, we suggest some policies that would help to implement Moderate Plurilingualism.